(untitled) (Research, Society and Development, 2021)
Objective: To analyze the use of Health Surveillance tools by managerial nurses in the planning and evaluation process of Family Health Strategy teams in Northeastern Pará. Methodology: Qualitative study with 7 Nurses of Family Health Units. An interview and analysis using the Bardin and IRAMUTEC methods was performed using the Descending Hierarchical Classification and similarity analysis, producing six lexical classes represented in Dendograma, considering words with significance (p>0.05), according to total frequency (f) and chi-square (x²). Results were expressed in Dendrograma, tree of similarity and cuts of the interviews in matrix frames. Results: We obtained the cleavage of 151 text segments, taking advantage of 76.16%, 5361 words, 633 active, 95 supplementary and average of 35.5 per follow-up. Based on the similarity analysis, the word "No" is perceived as the central nucleus, linked to "Health Surveillance", "Health" and "Action", thus inferring a denial, lack, absence and/or a problematic in the analyzed context. Conclusion: The decentralization of responsibilities between municipalities did not allow performance to meet demands. The non-adherence, in the management and health care models, of the Health Surveillance tools in the Family Health Units of Northeastern Pará is evident, therefore, the non-adjustment of actions and services in the Family Health Strategy considering local characteristics.